First record of Pulvinaria aurantii Cockerell (Hemiptera: Coccomorpha: Coccidae) from India, with a key to species of Pulvinaria Targioni Tozzetti in India - Das, Anirban; Pramanik, Aniruddha; Das, Bijan Kumar (Zootaxa, 2025)
A soft scale insect, Pulvinaria aurantii Cockerell (Hemiptera: Coccomorpha: Coccidae), is recorded for the first time from India on Mangifera indica L., a new host plant record from a new host plant family. The species is probably native to Japan but has an invasive nature; it warrants special attention in India because it is attacking an economically important fruit crop. As it is quite similar to P. polygonata Cockerell, also present in India, a thorough description, illustration and images of its diagnostic features are provided to facilitate identification. Information on its biology, host plant, attendant ant and hymenopteran parasitoid is given. An updated identification key is provided to separate almost all the species of Pulvinaria currently known to occur in India.